TEACHERS' VIEWS ON THE USE OF MULTIMEDIA IN TEACHING AND LEARNING - Jelimun, Maria Olga; Julia, Eka Yulian (TELL - US JOURNAL, 2022)
Abstract. By using multimedia, teachers can boost the efficiency of their students' learning activities. To assist in the qualification of classroom activities, instructors must be more current in their media selections, which should include not just traditional media but also multimedia. Thus, it is vital to determine how multimedia affects classroom activities and what types of media are employed in the classroom as a learning aide. In this light, the purpose of this study was to ascertain teachers' perspectives on the use of multimedia in education. The research sample consisted of fifteen senior high school teachers, and the relevant school was located in Ruteng district, Manggarai regency, East Nusa Tenggara. Additionally, this research included a qualitative approach. The results were gathered by asking open-ended questions directly to instructors on the challenges and opportunities associated with integrating multimedia in the classroom. Keywords: Multimedia; Teachers' perspective